2019
DOI: 10.1016/j.ajoc.2019.100457
|View full text |Cite
|
Sign up to set email alerts
|

Ocular infarction following ethanol sclerotherapy of an arteriovenous malformation

Abstract: Purpose To illustrate a case of ocular infarction following percutaneous ethanol sclerotherapy of an orbital arteriovenous malformation. Observations The patient is a 31-year-old female who developed ocular infarction of the left eye with light perception vision, proptosis, ophthalmoplegia, and a cherry red spot following sclerotherapy of an orbital arteriovenous malformation. Fluorescein angiography demonstrated decreased arteriolar filling with vascular leakage, indoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…In the cohort, eleven patients (42.3%) presented with visual acuity impairments with 3 complete relief, 6 improvements. Despite that ischemic time is reported to be an indicator of poor prognosis of vision improvement 14 , our study clearly showed eradicating arteriovenous malformation using ethanol embolotherapy facilitated improvement of visual outcomes in the cases with vision impairment. The potential cause for the improved visual function may be the increased perfusion of retina after obliterating the stulas and reducing arterial steal.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…In the cohort, eleven patients (42.3%) presented with visual acuity impairments with 3 complete relief, 6 improvements. Despite that ischemic time is reported to be an indicator of poor prognosis of vision improvement 14 , our study clearly showed eradicating arteriovenous malformation using ethanol embolotherapy facilitated improvement of visual outcomes in the cases with vision impairment. The potential cause for the improved visual function may be the increased perfusion of retina after obliterating the stulas and reducing arterial steal.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous studies reported that treatment of AVMs fed by OphA is clinically challenging due to complex hypervascularity of AVMs and the risk of vision loss from OphA involvement 1,4,21 . Endovascular treatment is effective for AVMs 5,8,24 , and ethanol embolotherapy of periorbital and orbital AVMs improves symptoms to some extent 14,15,25 , and yet the overall results are not satisfactory. However, due to its close proximity to retinal central artery, which regulates visual acuity and extraocular movements, therapeutic approaches that are speci c for treatment of AVMs fed by OphA are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The side effects and complications arising from the use of sclerosants and embolization agents has been well-reported [51][52][53][54][55][56]. Forty-three of the 56 articles included a description of the complications arising during or after the procedures.…”
Section: Plos Onementioning
confidence: 99%